KEDUDUKAN SUROGASI DAN STATUS HUKUM ANAK DALAM PERSPEKTIF HUKUM PERDATA DI INDONESIA - lintang wistu malindi; Mochammad Najib Imanullah (Jurnal Privat Law, 2021)
This study aims to analyze the legal standing of Surrogacy and the legal status of the child which is born by surrogacy based on Indonesia’s Private Law. In order to achieve the goal, the writer used normative legal research as a method. It used secondary data which consist of primary sources and secondary sources which obtained by doing literature study. The primary sources was composed of legislation, meanwhile its secondary sources was composed of publication such as books and other publications which related to the matter. It used statute approach and law interpretation in order to achive an answer. Based on the study, it shows that such surrogacy is unlawful and the legal status of the child which was achieved through the method still remains unclear based on Indonesia’s Private Law. Keyword: Surrogacy; Legal Status of The Child; Private Law